Peranan Pendidikan Formal Terhadap Aspek Kehidupan Politik - Yahya Yahya (UIN Sultan Aji Muhammad Idris Samarinda, 2009)
Formal education is the education which is developed at certain school or place systematically which has certain time sequence from Elementary to University level. Whereas the aspect of education life is one of the aspects in society that always develop and change to be more advance as the increasing of politic consciousness in society.This article concerns with the role of formal education to the aspects of politic life where the education is implemented based on the existing politic system by virtue of Pancasila (the five basic principles of the Republic of Indonesia) and UUD 1945, it means that politic determines the education policy. On the contrary, the existing politic system is determined by the education title owned by society where the higher education level of society will impact the consciousness to help forward the aspect of politic life in society. It is because formal education is one of media to socialize politic and great strategy to transfer the wide knowledge to the elite politic by giving training and also other facilities to build politic consciousness. It is the right moment to commit integration especially in terms of national politic consciousness.